Pengembangan Kurikulum PAI Madrasah Aliyah Berwawasan Multikultural - Akhyar Akhyar (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
Social conflict, discrimination, religious conflict, political crisis, economy, culture and education, becoming more frequent. With the presence of religion, the phenomenon of life can be given meaning and moral and transcendental, so as to have its own value. While the structure of the system in the form of religion or system of teachings and rules of functioning enforce social norms, rules, fulfilling the spiritual needs of man and God. But what about the religion (Islam) may be a solution to the conflicts, both horizontally and vertically not place? One way to resolve the conflict and bring peace and love between people, is through education. This is where the importance of islamic educatuion-minded multicultural curriculum development.